The influence of reconstruction following hemiglossectomy on perioperative outcomes - Nathan, Richa; Burmistrova, Michelle; Ata, Ashar; Gildener-Leapman, Neil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Hemiglossectomy can be required for oral cavity squamous cell carcinoma (OCSCC) resection but can result in functional and aesthetic deficits. Flap reconstruction is employed to restore form and function following hemiglossectomy but has procedure specific complications. Methods: Our study is a retrospective cohort study analyzing perioperative outcomes in patients undergoing hemiglossectomy with and without reconstruction using the American College of Surgeons’ national surgical quality improvement project (ACS-NSQIP) database. We identified 866 hemiglossectomy patients from 2008-2022, 233 of these patients underwent flap reconstruction. Modified Poisson regression was used to assess the effect of flap reconstruction on the risk of perioperative morbidity and mortality. Results: Patients who received reconstruction were 1.74 times more likely (95% CI: (1.31, 2.3) p<0.001) to have perioperative complications (pneumonia, ventilator use >48 hours, urinary tract infection, myocardial infarction, surgical site infections) and longer length of stay (10.71 vs. 3.67 days, p<0.001) compared to those without. American Society of Anesthesiology score (ASA) and neck dissection were found to be independent predictors of morbidity. In addition, the need for operative interventions like tracheostomy and neck dissection was more prevalent in the reconstruction group. The association was similar when limited to those who had concurrent neck dissection. Conclusions: Higher rates of complications associated with flap reconstruction among hemiglossectomy patients underscore the importance of careful consideration and surgical planning in flap reconstruction following hemiglossectomy. Understanding the relationship between perioperative risk and long-term functional outcomes will inform surgical decision making.